Effect of zirconia and chromia on the mechanical and tribology properties of alumina cutting tool - Abdul Manap, Muhamad Naim Fahmi (2021)
Due to their excellent hardness, high abrasion resistance and chemical stability, alumina based cutting tools are suitable for the high speed machining, which contributed to the high productivity. The properties of high hot hardness play significantly roles to perform in dry machining which further reduce operational cost. However, at some extent, alumina are prone to catastrophic failure, sudden breakage and thermal shocks due to brittle structure. Therefore, alteration of alumina composition with addition of Zirconia and Chromia is proposed to improve fracture toughness and wear resistance. In this research, the effect Zirconia and Chromia addition on the dimension accuracy, mechanical properties, tribology and wear performance were investigated. The study started with the mixture of Alumina-Zirconia with up to 25 wt% Zirconia content. These compositions were blended using ball mill, compacted using hydraulic and Cold Isostatic Press (CIP) and sintered at constant parameters. The mechanical properties of sintered Alumina-Zirconia were evaluated based on the dimension accuracy, density and hardness. The composition with maximum hardness was selected to be further composed with Chromia in range of 0.2-0.8 wt%. The result show that composition of Alumina–zirconia with ration 80-20 wt% presented maximum hardness of 70.07 HRC. With the addition of 0.6 wt% Chromia, the hardness was increased to 71.03 HRC. Further, composition that demonstrated highest hardness, which is Alumina-Zirconia-Chromia with the ratio of 80-20-0.6 wt% have been selected for machining tests. Machining trials with AISI 1045 carbon steel shows that Alumina-Zirconia-Chromia demonstrated maximum 360s tool life, which is 33.33% better that Alumina-Zirconia cutting tool. Wear mechanisme for both cutting tools dominated by the chipping, abrasive, built-up edge and built-up layer. Analysis shows that the addition of Chromia expanded Alumina particles and changed the overal grains distribution into bimodal structure. This provided Zirconia particles that infliltrated between Alumina particles interlocked overal structure, which facilitated into higher deformation resistance into overall structure. As potential application, cutting tool of Alumina-Zirconia-Chromia developed in this study suitable in machining low carbon steel up to 200 m/min cutting speed.